Navigating Bilingual Education in Democratic Settings: Identity, Integration, and Multicultural Awareness - Orak, Suheyla Demirkol (IGI Global, 2025)
This chapter critically explores bilingual and multilingual education policies in democratic societies through the lens of linguistic human rights, identity, and social justice. Drawing on Ruiz's (1984) framework of language as a right, problem, and resource, it examines how language ideologies embedded in policy and pedagogy can either reinforce systemic inequalities or foster inclusion. Using qualitative methods-including thematic analysis, document review, and comparative case studies from Canada, Spain, South Africa, and New Zealand-the chapter highlights both empowering and assimilationist models of bilingual education. It argues for a shift toward policies that value multilingualism as a societal asset, promote equity, and support identity formation. The study advocates educational reforms that ensure full participation of linguistically diverse learners in democratic contexts. © 2026 by IGI Global Scientific Publishing. All rights reserved.
Keywords: Bilingual education; Bilinguals; Education policies; Human rights; Identity integrations; Multi-cultural awareness; Qualitative method; Social justice; Thematic analysis; Through the lens; Linguistics